TINDAK PIDANA PERDAGANGAN ANAK DAN PEREMPUAN DI WILAYAH HUKUM KEPOLISIAN RESORKOTA BESAR MEDAN - Muhammad Iqbal Sinaga; Maidin Gultom; Bachtiar Simatupang (JURNAL PROINTEGRITA, 2019)
The purpose of this study was to determine the efforts made by the Medan City Police Resort in dealing with and dealing with trafficking, crime prevention efforts against trafficked children and women in Medan, legal protection for children and women victims of trafficking. in the Legal Territory of the Medan Big City Resort Police.The results of the study show that the factors that cause the crime of trafficking in children and women can be categorized into two factors, namely internal factors and external factors. Internal factors, including: individual factors, economic factors, family factors, and education factors. External factors, including: environmental factors, and the weak factor of law enforcement. Prevention and countermeasures carried out by the Medan City Resort Police in dealing with and dealing with the crime of trafficking in children and women are through law enforcement efforts and counseling to increase public knowledge. about the dangers of trafficking in persons.